Співвідношення та взаємодія актів тлумачення норм права з правозастосовчими та нормативно-правовими актами - Зубенко, А.В. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Проанализированы точки зрения ученых на данную проблему и сделан вывод о целесообразности выделения актов толкования в самостоятельный вид или группу правовых актов. Researches of the well-known scientists are analyzed in the article, an author considered their points of view on this problem and made an own conclusion in relation to expedience of separation of law interpretation acts in an independent kind or group of law acts.